2013
DOI: 10.3390/ijms141223980
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of 4-Methylcyclopentadecanone on Edema Models in Mice

Abstract: The present study evaluated the anti-inflammatory effects of 4-methylcyclopentadecanone (4-MCPC) on edema models in mice and aimed to determine the safety of 4-MCPC after acute exposure. The acute toxicity of 4-MCPC was evaluated by oral administration to rats of single doses of 0, 5, 50, 500 and 5000 mg/kg. Toxic symptoms were observed for 14 days. The anti-inflammatory activity was evaluated in xylene-induced mouse ear edema and carrageenan-induced mouse paw edema. The animals were treated with 4-MCPC once e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 32 publications
2
33
1
Order By: Relevance
“…The mice were divided into five groups of six each, as described in Table I, and inflammation was induced on the right ear of each animal while maintaining the left ear as an internal control (25). Edema was quantified as the weight difference between earplugs obtained from the two ears of the same animal.…”
Section: Pharmacodynamic Evaluation: Anti-inflammatory Effectmentioning
confidence: 99%
“…The mice were divided into five groups of six each, as described in Table I, and inflammation was induced on the right ear of each animal while maintaining the left ear as an internal control (25). Edema was quantified as the weight difference between earplugs obtained from the two ears of the same animal.…”
Section: Pharmacodynamic Evaluation: Anti-inflammatory Effectmentioning
confidence: 99%
“…However the neuroprotective activity of 4-MCPC was exhibited via activating the PI3K/Akt signal pathway. It is generally known that inflammation plays a crucial role in cerebral I/R injury, and our previous study testified that 4-MCPC has potent anti-inflammatory activity via decreasing the levels of IL-1b, TNF-a, PGE2, and MPO (17). So we speculate that the neuroprotective effects of 4-MCPC may also be related with the anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 54%
“…4-Methylcyclopentadecanone (4-MCPC) is a by-product of the synthesis process of muscone that was discarded in the past. Experimental studies have shown that 4-MCPC has similar effects on antiinflammation, antidementia, and antioxidation as muscone (16,17), and it was used to treat ischemic cerebrovascular disease in a patent in China. However, the neuroprotective effects and the associated mechanisms of 4-MCPC have not been explored in an I/R injury model.…”
Section: Introductionmentioning
confidence: 99%
“…A dose range of 10, 50, and 100 mg/kg of muscone was used for the low-, middle-, and high-dose groups, respectively. The selection of the doses was based on preliminary experiments of acute oral toxicity as demonstrated by previous studies [18]. The mice were sacrificed 6 or 12 days after the end of the treatment period and tissues from liver and kidney organs were obtained for western blotting, real-time PCR, and immunohistochemistry experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured in the DMEM solution containing 10% FBS in the presence of antibiotics (Pen/Strep 100 μg/mL) and 5% CO 2 as described previously [18]. The cells were passaged every 2-3 days.…”
Section: Methodsmentioning
confidence: 99%